2003
DOI: 10.1017/s0266467403003638
|View full text |Cite
|
Sign up to set email alerts
|

The need to be eaten: Balanites wilsoniana with and without elephant seed-dispersal

Abstract: This study demonstrates that elephant seed-dispersal is vital for Balanites wilsoniana (Zygophyllaceae), a forest canopy tree with no other effective dispersers. Non-dispersed seeds suffered high mortality (84%) and low germination (3%). Elephants were reliable at visiting fruiting trees (46%), ingesting available seeds (55%) and dispersing the fruit crop (26%). Compared with unpassed seeds, seeds passed through an elephant's gut had improved germination (54.9% vs. 2.9%) and reduced time to germination (82 vs.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
62
0
2

Year Published

2006
2006
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(66 citation statements)
references
References 34 publications
(42 reference statements)
2
62
0
2
Order By: Relevance
“…There is no evidence of any plant completely dependent on Asian elephants for seed dispersal. Such narrow mutualisms are exceptional in nature but have been described for African elephants and Balonites wilsoniana (Chapman et al 1992;Cochrane 2003;Babweteera et al 2007); and suggested for greater one-horned rhinoceros and Trewia nudiflora (Dinerstein 1988). Asian elephants can disperse seeds by endozoochory over long distances (CamposArceiz et al, unpublished).…”
Section: Discussionmentioning
confidence: 98%
“…There is no evidence of any plant completely dependent on Asian elephants for seed dispersal. Such narrow mutualisms are exceptional in nature but have been described for African elephants and Balonites wilsoniana (Chapman et al 1992;Cochrane 2003;Babweteera et al 2007); and suggested for greater one-horned rhinoceros and Trewia nudiflora (Dinerstein 1988). Asian elephants can disperse seeds by endozoochory over long distances (CamposArceiz et al, unpublished).…”
Section: Discussionmentioning
confidence: 98%
“…Our study, based on an examination of gut treatment, provides few studies comparing removal of passed and non-passed seeds, or seeds embedded or non-embedded in feces, do not yield a clear or consistent picture of any impact of gut passage on seed predation (Andresen 1999, Bermejo et al 1998, Cochrane 2003, Fricke et al 2013, Mártinez-Mota et al 2004, Roberts and Heithaus 1986. Furthermore, at least some observed impacts from these studies are inconsistent between seasons (Mártinez- Mota et al 2004) or within a season (Andresen 1999).…”
Section: Discussionmentioning
confidence: 94%
“…crude proteins) occurs at a greater rate in the presence of elephants (Scholes & Mennell, 2008). Additionally, elephants promote seed dispersal and germination (Cochrane, 2003).…”
Section: R Esum Ementioning
confidence: 99%